160 Gait Adaptability in Older People and People with PD. (20th December 2019) - Lord, Stephen; Caetano, Joana; Menant, Jasmine
Abstract: The ability to adapt gait when negotiating unexpected hazards is crucial to maintain stability and avoid falling. This presentation will present findings from a series of studies that have investigated cognitive, physical and psychological factors associated with gait adaptability required for obstacle and stepping target negotiation in older people and people with Parkinson's disease (PD). The first studies involved fifty healthy older adults (mean±SD: 74±7 years). The gait adaptability protocol required them to either (a) avoid an obstacle at usual step distance or (b) step onto a target at either a short or long step distance projected on a walkway two heel strikes ahead and then continue walking. The primary findings were that gait adaptability was significantly associated with high risk of falls and that executive function, increased concern about falling and weaker quadriceps strength contributed significantly to this relationship. The second studies involved 54 people with PD (mean±SD: 67±67 years) who also completed the gait adaptability protocol. In this group, superior executive function, effective reactive balance and good muscle power were associated with successful gait adaptability. Furthermore, executive function and reactive balance appeared to be particularly important for precise foot placements; and cognitive capacity for step length adjustments for avoiding obstacles. These findings help elucidate mechanisms for why older people and people with PD fall. Training gait adaptability directly, as well as addressing the above associated factors through cognitive, behavioural and physical training may maximise fall prevention efficacy for these populations.